2023
DOI: 10.3389/fcell.2023.1153174
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA abnormalities and metabolic syndrome

Abstract: Metabolic syndrome (MetS) is a complex pathological condition that involves disrupted carbohydrate, protein, and fat metabolism in the human body, and is a major risk factor for several chronic diseases, including diabetes, cardiovascular disease, and cerebrovascular disease. While the exact pathogenesis of metabolic syndrome is not yet fully understood, there is increasing evidence linking mitochondrial dysfunction, which is closely related to the mitochondrial genome and mitochondrial dynamics, to the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…At the same time, insignificant decrease of mtDNA copy number was demonstrated in whole blood of SSc patients. It is known that most studies on mtDNA copy number in diseases associated with mitochondrial dysfunction demonstrate a decrease in mtDNA copy number compared to healthy controls (Ding et al, 2023;Malik, 2023). The previous study on the number of mtDNA copies in the peripheral blood of patients with SSc showed that mtDNA copy number was lower in SSc patients in comparison with healthy participants of the study (Movassaghi et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…At the same time, insignificant decrease of mtDNA copy number was demonstrated in whole blood of SSc patients. It is known that most studies on mtDNA copy number in diseases associated with mitochondrial dysfunction demonstrate a decrease in mtDNA copy number compared to healthy controls (Ding et al, 2023;Malik, 2023). The previous study on the number of mtDNA copies in the peripheral blood of patients with SSc showed that mtDNA copy number was lower in SSc patients in comparison with healthy participants of the study (Movassaghi et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…The double-stranded closed mtDNA molecule consists of a heavy outer ring (H) and a complementary light inner ring (L) that contain no introns [14]. At the same time, the D-loop (control region) is the most intense regulatory non-coding region of mtDNA, which contains the origin of replication of the H-strand.…”
Section: Mtdnamentioning
confidence: 99%